PERANCANGAN APLIKASI UJIAN ONLINE BERBASIS WEB DENGAN METODE WATERFALL SEBAGAI SARANA EVALUASI PEMBELAJARAN PADA SMK INSAN KAMIL TARTILA - Ayu Juwita Sari; Santosa Wijayanto (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
SMK Insan Kamil Tartila is an educational institution where it should aim to implement an effective, efficient, and flexible curriculum. Exams at school become the basis for the evaluation that the school conducts on students. Conventional exams require longer preparation compared to online exams, then consume more papers, as well as a long processing time. This research is proposed to be based online at SMK Insan Kamil Tartila as one of the solutions to school needs. Exam system activities carried out online are considered more helpful from several aspects than conventional examination systems. The method used in the website creation process is Waterfall. With the stages of making needs analysis, system & software design, programming and application, system integration and trial, monitoring and system maintenance. The result of this research is a website that can facilitate the online exam process so that it is easy to apply, effective in implementation & minimizes the expenditure of funds.